Nine perfect strangers - Moriarty, Liane (New York Flatiron Books, 2018)
The retreat at health and wellness resort Tranquillum House promises total transformation. Nine stressed city dwellers are keen to drop their literal and mental baggage, and absorb the meditative ambience while enjoying their hot stone massages. Watching over them is the resort's director, a woman on a mission to reinvigorate their tired minds and bodies. But quite a different one from what any of the guests might have imagined. For behind the retreat's glamorous facade lies a dark agenda. These nine perfect strangers have no idea what is about to hit them.
Keywords: Strangers -- Fiction; City dwellers -- Fiction; Health resorts -- Fiction; Interpersonal relations -- Fiction; Psychological fiction